Indek Gingiva sebagai Indikator Klinis Akurat di dalam Pencerminan Kualitas Host pada Penyakit Periodontal - Mohamad Rubianto (Faculty of Dentistry, Universitas Indonesia, 2015)
Multifactorial is the etiology of periodontal diseases and there is homeostasis in balance from host and local factor. To determine the diagnosis and etiology accurately, ideal examination clinically radiographically and laboratorically should be done. SInce laboratoric xamination is expensive, we need to search a naccurate clinical indicator which can reflect the internal equality to the external local factors. The purpose of this study was to prove the equality of the clinical indicator (gingival index) to the laboratoric indicator, especially associated with regeneration and host resistance. Nineteen patients with periodontal disease for whom ginigvectomy was indicated were divided into 2 groups: the first group got gingivectomy with the application of periodontal pack, while for the second group sterile gauze was applied as control. Excised gingiva was examined pathobiologically for PMNL. macrophages, lymphocytes and fibroblasts. The examination was done on day 1, 5 and 7 after gingivectomy of the 2 groups. The Anova and Multiple Regression Test showed an equality of GI to the laboratoric component examined.